2020
DOI: 10.17718/tojde.727979
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning: A New Approach to Teach Ballet Technique for Undergraduate Students

Abstract: This study aims to investigate and compare the effect of the Blended Learning (BL) approach to Face to Face (FTF) teaching method on students' level of performance and sport participation motivation level. It is a qualitative study using the quasi-experimental method and applying the pre-test/post-test two-groups design model. The participants of this study were 40 female undergraduate students of School of Physical Education/University of Jordan. They were beginners enrolled in ballet classes with no previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…(3) In terms of learning effectiveness, there was a significant difference in learning effectiveness between blended learning and single type learning (−5.994, p < .05), and the average value of 4.307 was greater than that of single type learning (3.752). These results are consistent with those of many studies (Alsalhi et al, 2019;Baragash & Al-Samarraie, 2018;Bayyat, 2020;Farahani et al, 2020;Kingpum et al, 2015;Li et al, 2019;Vernadakis et al, 2012), students who use blended learning are satisfied with their learning effectiveness. In the process of the implementation of blended teaching, the resources of network and multimedia are integrated.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…(3) In terms of learning effectiveness, there was a significant difference in learning effectiveness between blended learning and single type learning (−5.994, p < .05), and the average value of 4.307 was greater than that of single type learning (3.752). These results are consistent with those of many studies (Alsalhi et al, 2019;Baragash & Al-Samarraie, 2018;Bayyat, 2020;Farahani et al, 2020;Kingpum et al, 2015;Li et al, 2019;Vernadakis et al, 2012), students who use blended learning are satisfied with their learning effectiveness. In the process of the implementation of blended teaching, the resources of network and multimedia are integrated.…”
Section: Discussionsupporting
confidence: 91%
“…As discussed in subsection 2.2, numerous studies (Alsalhi et al, 2019; Baragash & Al-Samarraie, 2018; Bayyat, 2020; Farahani et al, 2020; Kingpum et al, 2015; Li et al, 2019; Vernadakis et al, 2012) have determined that blended learning aids in increasing learning effectiveness. Due to the changes in teaching modes enacted because of the COVID-19 pandemic, PE courses could not be taught using conventional face-to-face learning and could only be taken through online learning.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With blended learning, learning will be designed in a mix between face-to-face and online, preceded by careful analysis of which material should be done faceto-face, and which can be done online. Several previous studies found that blended learning provides easy access, succes, and more varied learning environment [3], and blended learning proved to be an efficient and convenient methodology in terms of enhancing students' level of performance and boost their motivation for sports (ballet) participations [1]. The purpose of this study is to develop a blended learning model of Javanese classical dance learning.…”
Section: Introductionmentioning
confidence: 99%